The Correlation between Students' Reading Strategies and Reading Comprehension Achievement - Siti Rahma Adawiah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This research aims to find out the correlation between reading strategy and reading comprehension achievement. This research used a quantitative approach with a correlation design. The sample consisted of 80 accounting students in the sixth semester of the economics faculty at the University of Islam in Malang. The data was collected by using a reading strategies questionnaire and a reading comprehension test. Then, the data was analyzed by applying Pearson Product Moment Correlation analysis. The findings of the research showed that there was a positive significant correlation between reading strategies and reading comprehension because the significance shown on the table was 0.000<0.05 level of significance. In addition, the significant correlation between reading strategies and reading comprehension achievement shows that the more students use strategies in reading, the better their reading comprehension is.